The effect of short-term exposure to red and blue light on the autonomic tone of the individuals with newly diagnosed essential hypertension - Pratibha Modi (Journal of Family Medicine and Primary Care, 2019)
The research study aimed to study the effect of short term exposure to light basically red, blue and white on the autonomic tone of essential hypertensive individuals. The objective was to find out the baseline cardiac autonomic function along with the effect of these lights on the cardiac autonomic function among them. Till date few if any study have been conducted upon the individuals with certain disorder as common as essential hypertension. This was a cross sectional observational study conducted in the institute itself that included 77 newly diagnosed hypertensive subjects who willingly participated in the study. After written informed consent, brief history taking with the help of self-made questionnaire and clinical examination, they were randomized to different intervention groups (IG) namely IG I (red) IG II (blue) and IG III (white). HRV analysis of the last 5-6 minutes of both the baseline and color exposure was finally analyzed using MS Excel version 13 and Graph Pad Prism version 7.05. Different HRV parameters have been found to be affected differently on different color exposures. Red has shown to have an impact, mainly on the sympathetic system whereas white showed a dominant vagal component thus acting as a parasympathetic regulator. On one hand, where no conclusive result was found on blue light exposure, white light showed the most prominent results affecting various time and frequency components of HRV like SDRR, TP, LF etc. The present study, both, contradicts as well as supports various other works done on the similar area of interest. One reason of such high variation in different results is because HRV is itself a very dynamic function affected by even a slight change in both the internal and external environment of the subject. As artificial lights of various colors are part and parcel of the aesthetics and designing of most of the work environment all over world, it is very pertinent to study its impact upon human health status. The outcome of the study may play a decisive role in the diagnostics and therapeutics of essential hypertension in days to come. Furthermore, on the basis of the present findings, a future study could be undertaken with bigger data base addressing the limitations of the present study to find some conclusive evidence in the area highlighted.